Trust Management Frameworks for Decentralized Digital Ecosystems (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
Decentralised ecosystems claim to eliminate trust -- "don't trust, verify" is the mantra. But trust has not been eliminated; it has been redistributed. Users trust smart contract code they cannot read. They trust auditors they have never met. They trust oracle networks to feed honest data. They trust governance token holders to vote responsibly. They trust bridge validators not to collude. Every layer of a decentralised ecosystem contains trust assumptions, and when those assumptions fail -- as they did in the Terra/Luna collapse, the FTX fraud, and dozens of bridge exploits -- the consequences fall on users who did not understand what they were trusting. We present the Decentralised Trust Management Framework (DTMF), a systematic model for identifying, measuring, and managing trust across five layers of decentralised ecosystems -- protocol, smart contract, oracle, governance, and operational. We evaluate six trust management strategies -- formal verification, economic security analysis, oracle redundancy, governance decentralisation metrics, operational transparency scoring, and composite trust scoring -- on 20 real DeFi protocols. Our Trust Quality Index (TQI) shows that protocols combining formal verification with economic security analysis achieve the highest trust scores (TQI 0.908), while governance trust remains the weakest layer across the ecosystem with a mean score of only 0.584.